Identification of Hazardous and Toxic Waste Characterization in the Mining Activities of PT Semen Padang - Armando Yosephin Butar Butar; Ahmad Ikhsan; Abdul Razak; Linda Handayuni; Elsa Yuniarti (Science and Environmental Journal for Postgraduate, 2023)
Mining business activities in addition to producing mineral and coal production, also produce solid and liquid hazardous and toxic waste materials that have the potential to pollute the environment and can reduce the quality of human health and other living things mining. PT Semen Padang as the holder of a Production Operation Mining Business Permit (IUP OP), in addition to producing mining commodities in the form of limestone, silica, and clay, also has the potential to produce hazardous and toxic waste materials from mining activities, especially from the results of activities in mining workshops, both solid waste and liquid waste. For this reason, it is necessary to properly manage hazardous and toxic waste materials. PT Semen Padang has now carried out hazardous and toxic waste disposal by temporarily storing the hazardous and toxic waste it produces which is stored in a temporary storage area for hazardous and toxic waste materials.